Connectivity for Human Capital : Realizing the Right to Education and Healthcare through Improved Public Transport in African Cities - World Bank (World Bank, Washington, DC, 2021)
Despite having made tremendous progress in ensuring equal access to education and healthcare for its people, with school enrollment rates rising and children in most countries receiving the recommended preventative care, many countries in Sub-Saharan Africa (SSA) remain at the bottom of the World Bank’s Human Capital Index and the United Nations (UN) Human Development Index. The existing data also suggests that women are being overlooked in the drive to develop human capital, and only slightly over half of all primary school students continue schooling until lastgrade. Issues of access loom large; millions of children are not in school at all. This study aims to shine light on the extent to which the national level commitments to ensuring education and health for all are reflected in concrete transport, education, and health sector policies and targets at the country and city level and, in turn, whether the reality on the ground in some of the major urbanized areas in SSA is one of equal and adequate access. Focusing on ten large cities across SSA and applying not only spatial modeling tools but also policy and survey analysis and insights from interviews with human rights and development practitioners working in the region, the study provides new evidence on the degree to which health and education opportunities can be physically reached using the existing fixed route public transport systems. In doing so, it also identifieswho is being left behind – both across the urban space as well as across different dimensions of marginalization such as poverty, disability, gender, or their intersection. Because of the focus on public transport modes – mostly buses and minibuses – and walking, the results should therefore be interpreted as relevant for most, but not all, of the city populations, as accessibility by private cars or motorcycles is likely be higher although will certainly come up against congestion constraints if all or even most people were to rely on these modes. Recognizing that the use of health servicesand ability to meaningfully take advantage of education opportunities may be only partly driven by physical access barriers, the study also highlights the broader constraints faced by certain marginalized groups. Awareness of the role of transport connectivity and improved transport and land use planning coordination in facilitating access to essential services is noted in nearly all of the Government-level – both national and city-specific – policy documents and future strategies. At the same time, the differentiated education and healthcare access needs of the more vulnerable society groups – and targeted strategies on how to serve them – have received less attention, and the definition of sector-specific goals is not commonly informed by analysis of the existing spatial patterns of exclusion.